Hydrophilic or Lipophilic Statins? - Climent, Elisenda; Benaiges, David; Pedro-Botet, Juan (Frontiers in Cardiovascular Medicine, 2021)
Drugs can be classified as hydrophilic or lipophilic depending on their ability to dissolve in water or in lipid media. The predominantly lipophilic statins (simvastatin, fluvastatin, pitavastatin, lovastatin and atorvastatin) can easily enter cells, whereas hydrophilic statins (rosuvastatin and pravastatin) present greater hepatoselectivity. Although the beneficial role of statins in primary and secondary cardiovascular prevention has been unequivocally confirmed, the possible superiority of one statin or other regarding their solubility profile is still not well established. In this respect, although some previously published observational studies and clinical trials observed a superiority of lipophilic statins in cardiovascular outcomes, these results could also be explained by a greater low-density lipoprotein cholesterol reduction with this statin type. On the other hand, previous studies reported conflicting results as to the possible superiority of one statin type over the other regarding heart failure outcomes. Furthermore, adverse events with statin therapy may also be related to their solubility profile. Thus, the aim of the present review was to collect clinical evidence on possible differences in cardiovascular outcomes among statins when their solubility profile is considered, and how this may also be related to the occurence of statin-related adverse effects.